Film Hidden Figures Dalam Kajian Pendekatan Aliran Feminisme - Sheila Ayu Talissa; Nur Amathias Sari Gadis; Ginar Ayuningtyas (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2021)
Hidden Figures is a movie based on true story events set back in 1961 in the United States of America. The movie depicts three black women who fought for discrimination issues at the Langley Research Centre, NASA, Virginia, United States of America. This study uses a feminism theory as the basis for Sara Mills' discourse analysis which focuses on women's issues in the work environment, social life, class, race and biology. This research uses a qualitative communication method and Mills' critical analysis approach by using the subject-object and audience concept by looking at the dialogue, facial expressions and body language in the movie scene. Subject indicates the action narration of women's struggle in rejecting patriarchy are represented by the discourse and movements which carried out by the subject where women take actions to express the opinion so they can be positioned in regards skin color and men in their social environment (e.g work and education). The position of the object is described as an actor supporting the movement of the subject and as a party controlled and controlled by the subject. In addition the results of the present study show scene and dialogue relevant to several of feminism applications such as multicultural, cultural, radical, and postmodern feminism.